Analytical View of Suleyman Yudakov's Opera "Maysara's Work" - Akbarovich, Rajabov Avaz (International Journal on Integrated Education, 2023)
The article analyzes the life and work of campazitor Sulaymon Yudakov, who created the first Uzbek comic, and the creation of the first opera he created, "Maysara's Work", based on written sources.